Development of a database of sorghum cultivars in southern Africa, with emphasis on end-use quality, particularly brewing quality - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.